Metric analysis of the Revista de la Facultad de Agronomía de la Universidad del Zulia (2011-2021) - Chaparro-Martínez, Exio; Useche-Castro, Lelly; Rumbaut-León, Felipe; Quindemil-Torrijo, Eneida (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
The Revista de la Facultad de Agronomía de la Universidad del Zulia (LUZ), is a publication of the Instituto de Investigaciones Agronómicas de la Facultad de Agronomía, (LUZ) Venezuela. The digital content of the journal is hosted on the web site https://produccioncientificaluz.org/index.php/agronomia and is indexed in national and international databases. The objective of this research is to analyze the editorial management of the Revista de la Facultad de Agronomía (LUZ) in the period 2011 to 2021 through a bibliometric analysis of authorship, production, and collaboration, emphasizing the identification of the main research topics, their relationship and the components that integrate them. A descriptive, longitudinal, retrospective study of trend (analyzes changes over time) was carried out using quantitative techniques. It is based on the theoretical and methodological framework provided by information metric studies. Searches were carried out in the Scopus database. Several computer programs were used for data processing: VOSviewer, bibliometrix and Publish or Perish. The journal has a total of 442 original papers, from 2010 to 2021, with a total of 1375 authors, with an average production for the period of 40 articles per year and an average of 4.43 authors per article.